E-lectra: A Bibliography for the Study and Practice of Legal, Court and Official Translation and Interpreting - Monzó, Esther (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
Scientific development presupposes the efficient communication of new findings. The increase in the number of academic journals and publications worldwide burdens scholars, also translation scholars, with the responsibility of keeping up to date with ever increasingly scattered relevant literature. On the other hand, legal translation professionals need to select and find specialised documentation and reference material, which the market addresses not to translators or interpreters but to law specialists. E-lectra is an electronic bibliographic database whose purpose is to help legal translation scholars and practitioners select and find relevant literature and documentation resources, and further help researchers to present their work by providing a powerful pool of formats and styles incorporated in an easy-to-use system for citing references in their works and adapting them to the conventions of different journals from the field of translation studies.